مسلم دنیا کےفیمنسٹ اہلِ فکر: فاطمہ مرنیسی کے افکار کاتنقیدی مطالعہ: Feminist Thinkers of the Muslim World: A Critical Study of the Thoughts of Fatima Mernissi (Al-Qamar, 2025)
Fatima Mernissi is regarded as one of the most prominent intellectual figures among Muslim women who sought to reinterpret the relationship between Islamic tradition, gender equality, and female identity from a fresh and critical perspective. Her writings are not limited to advocating for women's rights; rather, they offer a critical examination of Islamic history, Hadith, and social structures to demonstrate that gender-based discrimination stems not from the original spirit of religious texts, but from patriarchal interpretations imposed over time. Mernissi’s feminist interpretations reflect her commitment to ijtihad (independent reasoning), historical consciousness, and a renewed understanding of Qur’anic principles. This study aims to critically analyze her thought to assess whether her interpretations provide a constructive foundation for Islamic feminism or merely reflect the influence of Western ideologies.
Keywords: Islamic tradition, Quranic principles, Islamic Feminism, Western ideologies, Historical consciousness, social structures, Gender equality